2021
DOI: 10.1039/d1qo00758k
|View full text |Cite
|
Sign up to set email alerts
|

Facile and practical hydrodehalogenations of organic halides enabled by calcium hydride and palladium chloride

Abstract: Herein, a convenient hydrodehalogenation method was described by employing less-explored calcium hydride as the reductant. A wide range of organic halides such as aromatic bromides, aromatic chlorides, aromatic triflates, aliphatic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Traditionally, sodium hydride (NaH) is employed as a Brønsted base for deprotonation of acidic substrates. Our group has revealed that NaH could be activated as a reductant under the catalysis of palladium salt, to achieve a series of reduction reactions including debenzylation and deallylation, 25a 1,4-conjugate reductions of α,β-unsaturated carbonyl compounds, 25b and hydrodehalogenations of organic halides 25c (Scheme 1b ). As our continuing work in this area, we report herein the reduction of several kinds of N -heteroarenes through transfer hydrogenation with the NaH/Pd reductive system.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
“…Traditionally, sodium hydride (NaH) is employed as a Brønsted base for deprotonation of acidic substrates. Our group has revealed that NaH could be activated as a reductant under the catalysis of palladium salt, to achieve a series of reduction reactions including debenzylation and deallylation, 25a 1,4-conjugate reductions of α,β-unsaturated carbonyl compounds, 25b and hydrodehalogenations of organic halides 25c (Scheme 1b ). As our continuing work in this area, we report herein the reduction of several kinds of N -heteroarenes through transfer hydrogenation with the NaH/Pd reductive system.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%